Dear Cypress, in this problem y'(t)=2y(t) is not a correct equation.
The solution proves y'(t)+2y(t)=2t+3. The formula y(t)=c*exp(-2t)+t+1
was given in the question and by differentiating this formula with
respect to t you can deduce y'(t)=-2c*exp(-2t)+1. Substituting the
corresponding expressions for y(t), y'(t) into y'(t)+2y(t) and
simplifying one gets y'(t)+2y(t)=2t+3.
Cypress
15.12.20, 16:06
How did you found y'(t)=2y(t)? I don't get that.
Leave a comment
Thank you! Your comments have been successfully added. However, they need to be checked by the moderator before being published.
Comments
Dear Cypress, in this problem y'(t)=2y(t) is not a correct equation. The solution proves y'(t)+2y(t)=2t+3. The formula y(t)=c*exp(-2t)+t+1 was given in the question and by differentiating this formula with respect to t you can deduce y'(t)=-2c*exp(-2t)+1. Substituting the corresponding expressions for y(t), y'(t) into y'(t)+2y(t) and simplifying one gets y'(t)+2y(t)=2t+3.
How did you found y'(t)=2y(t)? I don't get that.
Leave a comment